Detection of Chlamydia trachomatis in military men with clinical complaints of urethritis - Castro, Cláudio R.C. de; Passos, Mauro Romero Leal; Pinheiro, Vandira M.S.; Barreto, Nero A.; Rubenstein, Irineu; Santos, Cláudio C.C. (Brazilian Journal of Sexually Transmitted Diseases, 2000)
This is a prospective study of thirty enale patients with urethritis who sought voluntarily the Division of Sexually -Transmited Diseases at the Medical Clinic of the Heahh Corps of a Military Uniltocated in Rio de Janeiro betwecn June. 1996 and February, 1997. The author's aim was to detect chlamydial infection in these parients. Uretra) content was collected in swab and examined though Lhe ELPA method (Elisa wilh íluorescent assessment). Chlamydial infection was found in 23.3% of the material. Using a questionnaire with social - demographic data and questions about sexual habits, he also tried to idemiíy behavioral factors which could have beco conducive to lhe infection, determine thc frequency of urelhritis among lhe maje military population at the base and try to bring about ao awareness 10 the problem of sexually transmitted diseases among the military. Toe author Stresscs the role of Chlamydia trachomacis as a participating agent in non-gonoeoccal urethritis among the military and the pressing agent in non-gonoeoccal urethritis among the military and the pressing need of educational programs for the prevention and contral of sexually - transmited diseases among quartered populations.